AL-ADDAD: POLA UNIK BAHASA AL-QUR’AN - Jaeni, Muhamad (IAIN Pekalongan, 2010)
Semantic system unique in Arabic language is very interesting to study, particularly in relational meaning, because there are some Arabic semantic system parts whose concept is different from others. The relationship among the meanings like in modern linguistic is called as synonymy, polisemi homonymy, and antonymy can be found in Arabic and Quranic linguistic. Therefore, semantic studies have been existed in the Quran since a long time ago before linguists formulated modern semantic  is not found in other language meaning fields, like al-addad. Concerned with the position of Arabic language as Quranic language, the existence of al-addad also influences its translation and exegesis. The existence of al-addad mode in the Quran is a proof that the Quran has superiority viewed from language side.